Correlation between structure and properties of annealed electroless Ni–W–P coatings. (June 2015) - Liu, H.; Yao, H. L.; Thompson, G. E.; Liu, Z.; Harrison, G.
Abstract : Ni–W–P coatings with different structures were prepared by electroless deposition. The correlation between the coating structure before and after annealing with hardness and corrosion resistance has been examined by microhardness measurement, potentiodynamic polarisation and corrosion weight loss tests, and by quantitative X-ray diffraction technology and scanning electron microscopy observation of the corrosion morphology. The results indicate that incorporation of tungsten (4–5 wt-%) in Ni–P deposits does not change the amorphous structure of the Ni–11·3 P (wt-%) coating or the mixed structure of the Ni–6·8 P (wt-%) coating, but it changes the Ni–5·1 W–9·3 P (wt-%) coating into a critical amorphous structure. The coating with a critical amorphous structure develops a higher degree of crystallisation, larger crystal size and smaller number of Ni3 P crystallites after annealing at >300°C. It also exhibits the highest peak hardness and the poorest corrosion resistance after annealing at 400°C compared with the other two structural coatings (e.g. amorphous and mixed structures).